Parasocial relationships with morally ambiguous media characters – the role of moral foundations - Michelle Möri; Dominique Stefanie Wirz; Andreas Fahr (Studies in Communication Sciences, 2023)
Parasocial relationships are examined in diverse contexts and with various media characters, from news presenters to fictional movie heroes. A popular character trope in recent productions is the morally ambiguous media character (MAC). MACs disrupt the dichotomy between hero and villain, simultaneously exhibiting moral and immoral behavior. MACs attracted the attention of researchers, but little is known about parasocial relationships with them. This study examines these relationships by applying a multidimensional morality approach. The five moral domains of care, fairness, loyalty, authority, and purity are considered for the media character and the viewers. The role of these moral domains in parasocial relationships with morally ambiguous media characters was examined through an online survey (N = 250). The results show that moral behavior generally and moral behavior in care, fairness, and loyalty increased the strength of parasocial relationships, regardless of the viewer’s moral foundations. The characters’ behavior in authority and purity did not influence the viewers’ general morality perception nor their parasocial relationships with them. The study contributes to the existing literature about MACs by considering viewers’ parasocial relationships, their moral foundations, and the perceived morality in each of the five moral domains.